Acculturation of Islam and Javanese Culture in Rontekan Arts: A Case Study of the Ronda Tetek Tradition in Gombang Village, Boyolali Distric, Central Java - Haryono, Satrio Dwi; Nisa Islami, Fajriatun (Parahyangan Catholic University, 2023)
This study explores the acculturation of Islam and Javanese culture manifested through the Ronda Tetek Tradition in Gombang Village, Sawit District, Boyolali District, Central Java. Initially employed for night patrols, Rontek has evolved into traditional musical instruments and ceremonial practices. Over time, it has acquired an Islamic dimension, transforming into a musical accompaniment for Qasidah or Islamic poems. Employing qualitative methods, including participant observation and in-depth interviews, this research investigates the integration of Islamic and Javanese cultural elements in the Rontek tradition. The findings reveal that Rontek in Gombang Village has undergone acculturation with Islamic traditions, giving rise to a distinctive synthesis known as Javanese Islam. Despite its antiquity, Rontek continues to maintain its allure in Gombang Village, preserving local traditions while embracing Islamic influences.